Optimization of auto lamp spraying trajectory based on improved PSO algorithm - Guo, Biyu; Chen, Wei; Zhang, Jingfeng; Wei, Qingyu (Chinese Automation Congress (Online), 2021)
In this paper, the optimization method of lamp spraying trajectory is studied, the parabolic coating thickness accumulation rate model is established, and a segmentation algorithm based on lamp spraying is proposed. Taking the deviation between the thickness of the overlapping area and the ideal thickness as the optimization objective, the width and the spraying speed of the two adjacent spraying paths are determined. An improved particle swarm optimization (PSO) algorithm based on edge recombination operator is proposed for the optimal combination of all spraying trajectories on the lamp surface. Simulation experiments and spraying experiments verify the feasibility of the algorithm.